Fabrication of SrFe12O19-P2O5-CaO-Na2O Bioactive Glass-Ceramics at Various Sintering Temperatures - Pratthana Intawin (2018)
© 2015 Copyright Taylor and Francis Group, LLC. The effects of sintering temperatures on the physical, and bioactivity of SrFe12O19 (SF)-P2O5-CaO-Na 2 O bioglass ceramics were investigated. XRD results confirmed the existence of the strontium ferrite and calcium phosphate phases. SEM images showed that grain size, and hardness were related to density and liquid phase present in the samples. A maximum coercivity value of 3138 Oe was obtained for the bioglass ceramic sintered at 600°C. The remanence (Mr) and saturation magnetization (Ms) of the bioglass ceramic sintered at 500°C possess the maximum value of 6.35 and 10.64 emu/g, respectively. Moreover, the apatite was formed on the surface layers of the bioglass ceramics confirming their biocompatibility.